Optimal timing for salvage surgery after definitive radiotherapy in hypopharyngeal cancer - Chun, Seok-Joo; Keam, Bhumsuk; Heo, Dae Seog; Kim, Kwang Hyun; Sung, Myung-Whun; Chung, Eun-Jae; Kim, Ji-hoon; Jung, Kyeong Cheon; Kim, Jin Ho; Wu, Hong-Gyun (Radiation oncology journal, 2018)
Use of radiotherapy combined with chemotherapy is increasing in hypopharyngeal cancer. However, many show residual tumor after radiotherapy. Timing for treatment evaluation and salvage therapy is essential. However, optimal timing for salvage surgery has not been suggested. In this study, we tried to evaluate optimal timing for salvage surgery. Patients who were diagnosed with hypopharyngeal squamous cell carcinoma between 2006 and 2015 were retrospectively analyzed. All patients received definitive radiotherapy with or without chemotherapy. Response of all treated patients were analyzed at 1, 3, and 6 months after radiotherapy. Any patients with progression before 6 months were excluded. A total of 54 patients were analyzed. Complete remission (CR) rates at 1 month (CR1), 3 months (CR3) and 6 months (CR6) were 66.7%, 81.5%, and 90.7%, respectively. Non-CR at 1 month (NCR1), 3 months (NCR3), and 6 months (NCR6) showed poor locoregional recurrence-free survival rates (1-year rates of 63.7%, 66.7%, and 0.0%, respectively) compared to CR1, CR3, and CR6 (1-year rates 94.3%, 88.0%, and 91.5%, respectively). Particularly significant differences were seen between CR6 and NCR6 (p < 0.001). Of 10 patients with NCR3, 5 showed CR at 6 months (NCR3/CR6). There was no statistical difference in locoregional recurrence-free survival between CR3 and NCR3/CR6 group (p = 0.990). Our data suggest half of patients who did not show CR at 3 months eventually achieved CR at 6 months. Waiting until 6 months after radiotherapy may be appropriate for avoiding additional salvage therapy.